Estimation of fraction of drug metabolism by a single UDP‐glucuronosyl transferase enzyme using relative expression factor. (30th September 2022) - Honda, Tomoyo; Obuchi, Wataru; Nishiya, Yumi; Shibayama, Takahiro; Watanabe, Kengo; Watanabe, Nobuaki
Abstract: The estimation of the contributions of UDP‐glucuronosyl transferase (UGT) isoforms to the overall metabolism still suffers from technical difficulties due to limited information on enzyme levels in recombinant systems and specific inhibitors, unlike the case for cytochrome P450s (CYPs). The protein expression levels of UGT in both recombinant system microsomes (RM) and human liver microsomes (HLM) were quantified using liquid chromatography‐tandem mass spectrometry, and the relative expression factor (REF) value of HLM to recombinant microsomes was estimated to evaluate the fractions of drug metabolism by a single UGT enzyme (fmUGT) of UGT substrates. The REF values of UGT1A1, UGT1A3, UGT1A9, UGT2B4, UGT2B7, and UGT2B17 were 0.228, 0.0714, 0.0665, 0.420, 0.118, and 0.0442, respectively. fmUGTs in HLM were estimated for several typical UGT substrates utilizing these values and metabolic clearances in RM. These values were comparable to the reported values estimated by various methods. This study provided useful information on REF values, which promote a robust estimation of fmUGT values for UGT substrates when evaluating the contribution of UGT isoforms to total metabolic clearance. Abstract :